Impact of the COVID-19 Pandemic on the Situation of Large Families in Poland - Bebel, Anna (Wpływ pandemii COVID-19 na sytuację rodzin wielodzietnych w Polsce, 2022)
The aim of the article is to show the impact of the COVID-19 pandemic on the living situation of large families. The study paid particular attention to the economic and housing problems, as well as the mental condition and challenges related to remote learning. The study was primarily empirical. The article presents the results of quantitative research extended by a catalogue of open questions, together with the results of research conducted by the “Three Plus” Association of Large Families in May 2020. Statistical methods were used to analyse the data. The living conditions (in most of the examined dimensions) of most families with many children deteriorated during the pandemic. The most important problems faced by such families were primarily related to the labour market (employment and running a business), and housing (related to a deterioration of the mental condition of family members). However, the families also indicated closer family relations, caused by forced isolation and slowed-down pace of life (lack of commuting, additional activities, and other activities outside the home). Overall, families with more children, and those living in smaller flats experienced the most difficult situation.
Econometrics = Ekonometria, 2022, Vol. 26, No. 4, s. 17-29
Keywords: pandemic; large families; economic situation; pandemia; rodziny wielodzietne; sytuacja ekonomiczna